2019
DOI: 10.1177/2158244019859955
|View full text |Cite
|
Sign up to set email alerts
|

Browsing the Web for School: Social Inequality in Adolescents’ School-Related Use of the Internet

Abstract: This article examines whether social inequality exists in European adolescents’ school-related Internet use regarding consuming (browsing) and productive (uploading/sharing) activities. These school-related activities are contrasted with adolescents’ Internet activities for entertainment purposes. Data from the Programme for International Student Assessment (PISA) 2012 is used for the empirical analyses. Results of partial proportional odds models show that students with higher educated parents and more books … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Her results supported the idea that cultural capital is transmitted from parents to their offspring as she found that the cultural activities that children engage in are mediated by parental cultural capital and do not experience any school effect. Similarly, Weber and Becker (2019) state that Bourdieu's theory of cultural and social reproduction is their theoretical framework and apply it to the digital domain to identify whether there is social inequality in school-related internet use by European adolescents in terms of consumption (browsing) and productive activities (uploading/sharing). This was a descriptive study using data from the Program for International Student Assessment (PISA) 2012 for the empirical analysis.…”
Section: The Cultural Reproduction Theory Versus the Cultural Mobility Theorymentioning
confidence: 99%
“…Her results supported the idea that cultural capital is transmitted from parents to their offspring as she found that the cultural activities that children engage in are mediated by parental cultural capital and do not experience any school effect. Similarly, Weber and Becker (2019) state that Bourdieu's theory of cultural and social reproduction is their theoretical framework and apply it to the digital domain to identify whether there is social inequality in school-related internet use by European adolescents in terms of consumption (browsing) and productive activities (uploading/sharing). This was a descriptive study using data from the Program for International Student Assessment (PISA) 2012 for the empirical analysis.…”
Section: The Cultural Reproduction Theory Versus the Cultural Mobility Theorymentioning
confidence: 99%
“…In contrast, the lower percentage of 12.86% appears for students with a mark of outstanding who respond "a lot" in TTM. Similarly, it is postulated that the existence of adequate technological resources and connections promotes students' positive perceptions towards the use of ICT [22]. Moreover, technological advances, duly evaluated and oriented towards students, would, as a consequence, see more active participation by them [45].…”
Section: Discussionmentioning
confidence: 99%
“…The use of computers at home and in school will decrease in terms of capacity over the medium grade for the teaching and learning, without appropriate hardware, software, and pedagogical design improvements by teachers [22]. Some authors have argued that the use of portable devices was more effective in learning than the use of computers, because it facilitated a mobile, ubiquitous, collaborative, and creative form of learning [23].…”
Section: The Influence Of Ict On Educational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…First, while online activities are heterogeneous, some are regarded as capital-enhancing activities because they can add value and be transferable resources. Under the positive multiplied effects from these capital-enhancing activities, individuals are attracted to jobs, finances, health, and political participation, and gain social, financial, political, and cultural capital; thus, they are likely to increase their chances of upwards mobility [19,38,41]. For example, there is a usage gap between work and educational activities (which have capital-enhancing effects) and recreational activities (which do not) [19].…”
Section: Hypothesesmentioning
confidence: 99%